Cues from chewing insects — the intersection of DAMPs, HAMPs, MAMPs and effectors. (August 2015) - Acevedo, Flor E; Rivera-Vega, Loren J; Chung, Seung Ho; Ray, Swayamjit; Felton, Gary W
Highlights: Upon feeding, herbivores secrete saliva, regurgitant and frass that come in contact with the plant. Herbivore's gut symbionts can also be released during feeding and recognized by the plant. The composition of these secretions and gut microbial community is dependent upon their host plant and the herbivore. Cues present in herbivore secretions are recognized by plants to trigger defense responses. Some of these cues can act as effectors or elicitors in a context dependent manner. Abstract : Chewing herbivores cause massive damage when crushing plant tissues with their mandibles, thus releasing a vast array of cues that may be perceived by the plant to mobilize defenses. Besides releasing damage cues in wounded tissues, herbivores deposit abundant cues from their saliva, regurgitant and feces that trigger herbivore specific responses in plants. Herbivores can manipulate the perception mechanisms and defense signals to suppress plant defenses by secreting effectors and/or by exploiting their associated oral microbes. Recent studies indicate that both the composition of herbivore cues and the plant's ability to recognize them are highly dependent upon the specific plant–herbivore system. There is a growing amount of work on identifying herbivore elicitors and effectors, but the most significant bottleneck in the discipline is the identification and characterization of plant receptors that perceive these herbivore-specific cues.